Broiler Chicken Performance with The Addition of Moringa Leaf Flour (Moringa oleifera) and Garlic Flour (Allium sativum L) - Gaol, Susan Lumban; Ida Ketut Mudhita (Bantara Journal of Animal Science, 2024)
This study aims to determine the effect of giving Moringa leaf flour at 1, 2.5% and 5% and garlic flour at 2% on the performance of broiler chickens. The materials used are 64 broiler chickens. Moringa leaf flour and garlic flour. This study used a completely randomized design with four treatments and four replications. P0 = 100% commercial feed, P1 = 1% Moringa leaf flour and 2% garlic flour, P2 = 2.5% Moringa leaf flour and 2% garlic flour, P3 = 5% Moringa leaf flour and 2% garlic flour for 35 days. The variables observed were feed intake, body weight gain, feed conversion ratio, mortality and performance index. The data obtained were analyzed using variance analysis, and the Duncan test was continued. The results showed that the treatment had no significant effect (P>0.05) on feed intake, weight gain, FCR, mortality and IP. Based on the study results, it can be concluded that administering Moringa leaf flour at up to 5% and garlic flour at 2% yielded good results on weight gain, FCR, and mortality.